Form of Verbal Emotion Regulation Expression of STKIP PGRI Ponorogo Students (Psycholinguistic Study) - Astuti, Cutiana Windri; Lusy Novitasari; Endah Normawati Mahanani (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
Emotions can be manifestations of affection, happiness, anger, annoyance, hatred, sadness, disappointment, fear, depression, and so on. In every emotion, humans can exercise emotional control or emotional regulation. Expressions of verbal emotional regulation can be in the form of positive or negative words, phrases or sentences depending on how emotional regulation each individual has. The aim of this research is to find out how STKIP PGRI Ponorogo students express verbal emotional regulation. The research method is descriptive qualitative. Where the researcher used a research instrument in the form of a questionnaire which contained five questions or situational contexts to collect research data related to the form of verbal emotional regulation expressions of STKIP PGRI Ponorogo students. Furthermore, the collected emotional data and forms of verbal expression of emotional regulation were analyzed using psycholinguistic studies. The results of data analysis in each situation context show that STKIP PGRI Ponorogo students are good when experiencing emotions of happiness, anger, sadness, anxiety and depression, expressing their verbal emotional regulation using positive and good sentences. The results of this research can add information regarding the sentences used by students in their verbal emotional regulation and can be used as reflection material for lecturers in improving the learning process..